PENGARUH PENENTUAN TARIF TERHADAP KINERJA KEUANGAN DAN KEPUASAN PELANGGAN PADA PDAM TIRTA ARDHIA RINJANI - OZWINA, SITI ZARA; SASANTI, ELIN ERLINA; PUSPITASARI, INDRI (Universitas Mahasaraswati K. Mataram, 2023)
This research aims to examine the effect of determining PDAM water tariffs on financial performance and customer satisfaction at PDAM Tirta Ardhia Rinjani, Central Lombok Regency. The theory used in the research is stakeholder theory which describes the relationships between individuals or groups who are affected by company activities or can influence the activities of a company. This research has a sample of 100 respondents who are active customers of PDAM Tirta Ardhia Rinjani Kab. Central Lombok. The data analysis uses descriptive statistical tests, classical assumption tests, t tests, F tests and coefficients of determination as well as the help of SPSS 25 analysis tools. The results of research using simple linear regression analysis show that the tariff determination variable (X) does not have a positive effect on financial performance (Y1) and customer satisfaction (Y2) at PDAM Tirta Ardhia Rinjani Kab. Central Lombok.